Implementation of Principal Academic Supervision in Improving the Performance of Islamic Religious Education Teachers - Maryati, Maryati; Asra, Muhammad; Iqbal, Muh. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of the principal's academic supervision in improving the performance of Islamic Religious Education (PAI) teachers at MTs Al Mawaddah Warrahmah Kolaka. The research method used was descriptive qualitative with academic supervision approach. Data collection was conducted through interviews, observations, and documentation with the principal and PAI teachers as the main subjects of the research. The results showed that the academic supervision conducted by the principal has been running well, using various techniques such as clinical supervision, class visits, class observations, teacher meetings, evaluations, and follow-ups. Clinical supervision is the main method in providing guidance to teachers, while classroom visits and observations help in assessing teaching effectiveness. Evaluation is conducted periodically to assess the impact of supervision on improving teachers' professionalism. Follow-up in the form of individual coaching and additional training is also provided to teachers who still have shortcomings. The results of this study are in line with the theory of academic supervision which emphasizes the importance of guidance and monitoring in improving the quality of learning. Therefore, the implementation of systematic and sustainable academic supervision needs to be continuously developed to support the improvement of the quality of education in madrasah.